Metode Penelitian dan Pemahaman Hadis Musykil - Abd Wahid (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
It is said hadis musykil (dubious hadith) due to two main factors; difficulty  in understanding its content and its contradictory to the other hadiths or the  Qur’an. This kind of hadith has no problem with its sanad (narrators) to regard it  as valid hadith, sahih hadith. For this reason, the muhaddithin ulamas make  serious efforts to understand this kind of hadith. They also set theories and  methods to solve problems related to musykil hadith. Their efforts now become  one branch of ulum al-hadith so called al-`ilm musykil al-hadith.